Pembinaan UMKM Ekonomi Kreatif Guna Meningkatkan Manajemen Branding Dan Pemanfaatan Digutal Marketing Di Kelurahan Wonorejo - Fauziyah Imamah; Orell Xalansa Lubdiyanto; Lia Rizqy Wulantari; Ruthyanti Manihuruk; Bagus Ariz Faishal (FKIP, Universitas Palangka Raya, 2023)
Micro, Small and Medium Enterprises (MSMEs) contribute greatly to Indonesia's economic growth. To achieve a stable and sustainable economy, it is necessary to support solid macroeconomic stability. Empowerment of the real sector, especially the development of MSMEs. The purpose of this KKN activity is to provide branding and digital marketing management assistance for MSMEs in the Wonorejo Village. The partners in the thematic real work lecture program in the Wonorejo Sub-District are beginner MSMEs and have been starting a business for several months. The problems faced by MSMEs are digital marketing, packaging is still made in a simple way, and confusion about how to do branding. This problem arises because of the limited knowledge possessed by MSME actors, and the limited ability to use devices. This MSME actor mentoring activity aims to increase the knowledge and abilities of MSME actors in developing their business. MSME actors are given an understanding of the use of e-commerce and the importance of using technology in MSME product development so that they can increase income.